The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/tp.0b013e3181ba343a
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Procurement of Single Versus Multiple Artery Kidney Allografts: Is Long-Term Graft Survival Affected?

Abstract: Background Living donor kidneys with multiple arteries (MA) are increasingly procured laparoscopically for transplant. Methods We compare long-term graft function and survival of kidneys with single arteries (SA) and MA over a 10-year period. Results There were a total of 218 grafts with SA and 60 grafts with MA. The MA group had longer operative and ischemic times than SA group. There was a small increase in ureteral complication (8.3% vs. 2.3% P=0.06) and a significantly higher incidence of rejection (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…In the other hand, Paramesh et al when analyzing 278 LDN during a 10-year period, showed in a multivariable logistic regression analysis that MA was an independent risk factor for acute rejection. The authors also showed that the graft function at 6 and 12 months was significantly lower in the MA group than SA group, and this trend persisted for 3 years after transplant (13). In the present study, the MA group had a higher rate of poor EGF when compared to the SA group (23% vs 12%, respectively).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In the other hand, Paramesh et al when analyzing 278 LDN during a 10-year period, showed in a multivariable logistic regression analysis that MA was an independent risk factor for acute rejection. The authors also showed that the graft function at 6 and 12 months was significantly lower in the MA group than SA group, and this trend persisted for 3 years after transplant (13). In the present study, the MA group had a higher rate of poor EGF when compared to the SA group (23% vs 12%, respectively).…”
Section: Discussionsupporting
confidence: 57%
“…Results from previous studies comparing renal function outcomes in patients with MA and SA have been variable (13,(16)(17)(18)(19)(20). Kuo et al. showed similar functional outcomes for patients with one, two or three renal arteries.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The presence of multiple renal arteries, however, results in higher rates of ureteric complications in the recipient compared with kidneys with a single artery (16.7% vs 3.2%, P = 0.001) [46]. In addition, transplantation of kidneys with multiple arteries has been shown to produce higher rates of graft loss than in organs with single vessels (HR 2.30, 95% CI 1.05, 5.09, P = 0.038) [47]. As ‘pure’ and hand‐assisted right LDN have been shown to be feasible and safe [48,49], with shorter operative times than left LDN [50], right LDN is now regarded as an acceptable alternative to left LDN in the presence of multiple renal arteries supplying the left kidney but not the right [51].…”
Section: Anatomical and Technical Considerationsmentioning
confidence: 99%